Judicial Disparities in Premeditated Murder Cases: Legal Certainty in the Interpretation of Articles 338 and 340 of the Indonesian Criminal Code - Tanto Satryatama; Andika Wijaya; Satriya Nugraha; Rizki Setyobowo Sangalang (Journal Evidence Of Law, 2026)
Judicial disparities in homicide cases involving indications of premeditation continue to challenge legal certainty in Indonesia's criminal justice system. Previous studies have primarily examined sentencing disparity or the interpretation of Article 340 of the Indonesian Criminal Code (KUHP) in individual cases, but have not systematically explained the relationship between legal certainty, judicial discretion, and judicial reasoning through comparative analysis of judicial decisions. This study addresses that gap by analysing inconsistencies in the interpretation of the element "with prior planning" (dengan rencana terlebih dahulu) through a normative juridical method employing statutory, conceptual, case, and comparative approaches. The analysis focuses on Decision Number 230/Pid.B/2023/PN Sda and compares it with four homicide decisions rendered between 2021 and 2024 involving comparable factual circumstances. The findings reveal five principal factors contributing to judicial disparity: (1) the absence of objective parameters for interpreting Article 340 of the KUHP; (2) broad judicial subjectivity in assessing the offender's psychological condition; (3) the lack of interpretative guidelines issued by the Supreme Court; (4) inconsistency in judicial precedent concerning comparable cases; and (5) divergent interpretations regarding the interval between the formation of intent and the execution of the offence. These factors result in inconsistent legal qualifications and sentencing outcomes despite materially similar facts. The study's theoretical contribution lies in integrating the perspectives of legal certainty, judicial discretion, ratio decidendi, and sentencing disparity into a unified analytical framework for evaluating judicial interpretation of premeditation. Its practical contribution is the formulation of four cumulative objective indicators—weapon preparation, victim surveillance, preparation for escape or concealment, and sufficient time for rational reflection—as interpretative guidelines to support consistent application of Article 340. Accordingly, the study recommends the adoption of these indicators through a Supreme Court Regulation (Peraturan Mahkamah Agung—PERMA) to strengthen legal certainty while preserving judicial independence in homicide adjudication.